Analisa Kinerja Jalan terhadap Kecepatan Kendaraan di Ruas Jalan Lingkar Barat Tiga Kenali Besar Kota Jambi - Yamali, Fakhrul Rozi; Dony, Wari; Pratama, Aldion (Jurnal Talenta Sipil, 2024)
This research aims to identify the main factors that influence vehicle speed. Analyzing the level of service on the West Ring Road 3 in Kenali Besar, Jambi City. Researchers use quantitative methods where data is taken by carrying out direct observations in the field. The objects aimed at by researchers are road geometric data, vehicle volume, vehicle travel time, traffic volume and vehicle speed obtained by conducting surveys and direct measurements in the field. The main factor that influences vehicle operational speed is the number of motorized vehicles and heavy vehicles that exceed road capacity. Where the average number of light vehicles at peak hours is 8,434 and heavy vehicles 1,524. With the average highest speed of motorized vehicles being 30 KM/hour and heavy vehicles 15/14 KM/hour. Level of Service on the West Ring Road Section 3 with a Degree of Saturation value from the direction of Pall 10 - Simpang Rimbo or vice versa from the direction of Simpang Rimbo - Pall 10 has a service value of C (0.45-0.74) in the stable flow zone. Drivers are limited in choosing speed